"Dolore, nascita e morte" in una prospettiva multiculturale. Considerazioni formative su alcuni concetti chiave inerenti l'identità professionale degli infermieri - Carlo Orefice (Firenze University Press, 2013)
Despite nursing knowledge requires solid expertise in a wide range of fields (e.g. from clinical practice to the language of healthcare organizations, from different healthcare provision models to diverse ways of knowing the disease, up to a series of highly topical issues, such as medical errors, inormed consent, aggressive treatment, etc.), in this essay the author reflects, starting from his own ex- perience of university teacher and researcher in nursing, on three key-concepts (pain, birth, death) on which and through nurses have structured, not without contradictions, their professional identity.